The heterogeneous life space trajectories and predictors in stroke patients: a cohort study - Yang, Bei; Xie, Rui; Ge, Siyuan; Tang, Ruixue; Cheng, Kangyao; Wang, Yin (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to identify heterogeneous trajectories of life space among stroke patients and explore the predictors for different classes of life space.MethodsThis prospective cohort study assessed 210 stroke patients’ life space at baseline and 1, 3, 6 months post-discharge. We elucidated heterogeneous trajectories of life space by latent class growth model and explored the predictors of trajectories by multinomial logistic regression analysis.ResultsAmong 173 participants completing the 6-month follow-up, three distinct life space trajectories were identified: the “high-level recovery flat class” (8%), the “medium-level recovery good class” (72%), and the “low-level recovery poor class” (20%). Multinomial logistic regression, using the low-level recovery poor class as the reference, indicated that age <60, absence of limb sensory deficit, and positive environmental experiences were predictors of the medium-level recovery good class, whereas employment status and positive environmental experiences were predictors of the high-level recovery flat class.ConclusionThe three trajectories of life space indicated that the 1 month post-discharge is the most vulnerable phase for stroke patients. Age and employment status significantly influence life space trajectories. Patients in the low-level recovery poor class should receive special attention. Strategies to improve sensory deficits and environmental experiences should be developed to expand life space, promoting stroke patients’ rehabilitation.